2023
DOI: 10.3390/s23031082
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Resolved Elemental Analysis on Moving Electrode Foils with Laser-Induced Breakdown Spectroscopy

Abstract: In this study, a new method for the inline measurement of depth profiles on a continuously moving sample with laser-induced breakdown spectroscopy is presented. The ablation profile is generated by ablating the sample with a burst of laser pulses, where the emission spectrum of each laser-induced plasma is analyzed on a spectrometer. A Q-switched Nd:YAG laser at 1064 nm with 10 mJ pulse energy, 6 ns pulse duration and 100 Hz repetition rate was used. The focusing lens for the pulsed laser and a deflection mirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Two papers by the same research group have reported the use of LIBS for homogeneity measurements of lithium ion batteries 226 and for depth-resolved elemental analysis on moving foils. 227 In the former paper, a LIBS system operating at 1064 nm, a pulse duration of 6 ns and a varied pulse energy of between 0.25 and 50 mJ was used. Detection was achieved using three Czerny–Turner style spectrometers with ranges of 193–262 nm, 268–536 nm and 500–736 nm.…”
Section: Inorganic Chemicals and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers by the same research group have reported the use of LIBS for homogeneity measurements of lithium ion batteries 226 and for depth-resolved elemental analysis on moving foils. 227 In the former paper, a LIBS system operating at 1064 nm, a pulse duration of 6 ns and a varied pulse energy of between 0.25 and 50 mJ was used. Detection was achieved using three Czerny–Turner style spectrometers with ranges of 193–262 nm, 268–536 nm and 500–736 nm.…”
Section: Inorganic Chemicals and Materialsmentioning
confidence: 99%
“…The latter paper used the same setup, but concentrated on measuring depth-profiles on moving samples. 227 The focussing lens for the pulsed laser and a deflection mirror were mounted on a moving stage which was precisely aligned in height and orientation to the movement of a conveyor belt on which the sample was transported. The speed of the stage and the conveyor were synchronised to ensure the same spot on the sample was analysed each time.…”
Section: Inorganic Chemicals and Materialsmentioning
confidence: 99%
“…Multichromatic lasers can also be applied in coating inspection [4], depth-resolved measurement of element composition [5], and microwave and terahertz generation [6,7]. Additionally, the frequency of the emitted beams can be doubled or tripled through second and third harmonic generation (SHG and THG), leading to green, red, and blue emissions that are interesting for applications in Light Detection and Ranging (LIDAR) and range finding [2,8,9].…”
Section: Introductionmentioning
confidence: 99%